2021
DOI: 10.1108/bfj-10-2020-0901
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hedonic dining experiences on word of mouth, switching intentions and willingness to pay

Abstract: PurposeWhen customers decide to dine out, they choose a restaurant for both physiological and psychological reasons. The psychological reasons include the hedonic/enjoyment goal of the consumer. The purpose of this paper is to investigate whether dining experiences that provide a positive or negative hedonic value will influence positive word of mouth (PWOM), switching intentions (SI) and willingness to pay (WTP).Design/methodology/approachTwo survey-based experiments using student (N = 112) and general restau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Informativeness has a positive influence on the overall satisfaction of community members and their degree of identification with a virtual community. When users of SNSs use these sites to carry out a particular activity, they are looking for functional benefits [60,92]. Wu [61] reported that satisfaction with SNSs was positively affected by utilitarian value, while Ashraf et al [43] reported that it positively influenced the intention of Chinese users of social media to continue using this medium.…”
Section: Utilitarian Valuementioning
confidence: 99%
“…Informativeness has a positive influence on the overall satisfaction of community members and their degree of identification with a virtual community. When users of SNSs use these sites to carry out a particular activity, they are looking for functional benefits [60,92]. Wu [61] reported that satisfaction with SNSs was positively affected by utilitarian value, while Ashraf et al [43] reported that it positively influenced the intention of Chinese users of social media to continue using this medium.…”
Section: Utilitarian Valuementioning
confidence: 99%
“…Based on literature review and hypotheses development the research framework is presented in Figure 1. This research adopted the scenario-based experimental research design, as this research design is widely employed when investigating face-to-face WOM due to difficulty in observing offline WOM as it occurs (Chawdhary & Dall'Olmo Riley, 2015;East et al, 2001;Garnefeld et al, 2011;Sukhu & Bilgihan, 2021). In contrast to retrospective surveys, experimental research designs reduce biases stemming from memory lapses and have stronger internal validity (Wien & Olsen, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Luxury goods can be purchased as self‐gifts (Dubois & Laurent, 1996). In the context of hedonic consumption, deriving positive emotions during a consumption experience increases the willingness to pay for that experience (Sukhu & Bilgihan, 2021) or service (Izogo et al, 2021). Consumers who feel that their self‐determined needs—including the need for personal autonomy—are fulfilled exhibit more, rather than less, willingness to pay a premium (Gilal et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%